Organizational influences and performance impact of barriers to e-exporting: the moderating role of home country digital infrastructure and host country internet penetration - Leonidou, Leonidas C.; Eduardsen, Jonas; Marinova, Svetla; Christodoulides, Paul (My University, 2020)
Despite voluminous research on barriers to exporting, knowledge on the inhibiting role of specific obstacles confronted by firms when exporting their goods in a virtual rather than real spatial domain is absent. Using data from a sample of 1,816 firms located in 26 different European countries, we shed light on this issue by examining the organizational determinants and performance outcomes of barriers to e-exporting. The results revealed that these barriers are more evident in the case of firms with smaller size, lacking experience in international business, and having no affiliation with other companies. It was also found that all different types of e-export barriers, namely financial complexities, coping with foreign markets, supplier restrictions, technical difficulties, and product limitations, are negatively affecting online export performance. Finally, both the home country’s level of digital infrastructure and the host country’s internet penetration rate exhibited a strong moderating effect on the association between e-export barriers and export performance.